Mortality after partial left ventriculectomy in relation to contraindications for heart transplantation - Frota Filho,José Dario (2003)
OBJECTIVE:To analyze the impact of the contraindications for heart transplantation in mortality and survival time after partial left ventriculectomy. METHOD: A prospective clinical study of a cohort of 43 patients submitted to partial left ventriculectomy, in whom there were contraindications for heart transplantation was performed. The following contraindications were analyzed: psychological, sociocultural, age of 65 years of age and older, elevated pulmonary arteriolar resistance and pulmonary arterial hypertension and the refusal or not for transplantation. These variables were tested for association with postoperative mortality and survival time after partial left ventriculectomy. Statistical analysis included the Chi-square test, Kaplan-Meier survival analysis, non-parametric log-rank test, Cox regression model, 95% confidence intervals and p values (significant if less than 0.05). RESULTS: Higher postoperative mortality rates for partial left ventriculectomy were found when the following contraindications of heart transplantation were present preoperatively: poor sociocultural conditions (p = 0.037), psychological disturbances (p = 0.037) and in patients who accepted heart transplantation even when counseled against this procedure (p = 0.017). Survival time was significantly shortened in the presence of psychological disturbances (p = 0.0466), in patients older than 65 years (p = 0.0397) and in those who did not accept heart transplantation (p = 0.0306). Elevated pulmonary arteriolar resistance and pulmonary arterial hypertension were not associated with higher mortality rates or shortened survival time. CONCLUSION: Some of the contraindications for heart transplantation adversely affected the mortality and survival time after partial left ventriculectomy, thus revealing the ineffectiveness of this alternative procedure in this subset of patients.